Assessment of the enamel defects in primary teeth of premature infants - Sh Kakoei; B Bahman Bijari (Isfahan University of Medical Sciences, 2009)
Introduction: The aim of this study was to determine the prevalence of enamel defects in primary dentition of the term and preterm infants.Method and materials: In this historical cohort study, enamel defects (enamel hypoplasia and opacities) were evaluated and determined in 137 children (90 term, 47 preterm). Indeed, some data about weight, systemic diseases and medicine consumption in mothers and children and problems during delivery were achieved. Data were analyzed by chi-square test using SPSS software.Results: The prevalence of enamel defects of any type among these children was 27.7 percent, only hypoplasia 14.9 percent, and only opacities 14.9 percent. Enamel hypoplasia was more frequent in upper central incisors (14.9%) and lower first molars (10.6%). The prevalence of hypoplasia and opacities were more frequent in preterm children but results of χ² test did not show any significant difference. Breech presentation, infantile respiratory distress syndrome and hypoxia during delivery were more frequent in preterm children (P = 0.0001).Conclusion: This study showed that there is no significant difference in prevalence of enamel defects in preterm infants in comparison to terms.Key words: Enamel defect, primary dentition, prevalence, preterm children